2017
DOI: 10.1177/1073191117739017
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Reported BIS/BAS Scales for Children: Factor Structure and Measurement Invariance Across Age and Gender

Abstract: The present study examined the factor structure and measurement invariance of the Behavioral Inhibition System/Behavioral Approach System (BIS/BAS) scales parent-report in children and adolescents ( N = 1,444, 58% girls) across age (Group 1, 2-5 years; Group 2, 6-9 years; Group 3, 10-13 years; Group 4, 14-18 years old) and gender. The results consistently underscored a four-factor structure, resembling the original factor structure, with one BIS-factor and three BAS-factors. Multigroup confirmatory factor anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 75 publications
1
6
0
1
Order By: Relevance
“…Similar to previous studies, the BASFS subscale was less reliable in the current study. Further, the four-factor structure of the PR reported by Vervoort et al (2017) was confirmed for the PR2013. Remarkably, the fit was not adequate in 2011.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Similar to previous studies, the BASFS subscale was less reliable in the current study. Further, the four-factor structure of the PR reported by Vervoort et al (2017) was confirmed for the PR2013. Remarkably, the fit was not adequate in 2011.…”
Section: Discussionsupporting
confidence: 63%
“…A satisfactory external validity and Cronbach's αs of 0.76 for BIS, 0.86 for BAS, 0.85 for BASD, 0.74 for BASRR, and 0.57 for BASFS were reported. A principal component analysis supported the original four-factor structure (Vervoort et al, 2017).…”
Section: Methodsmentioning
confidence: 67%
“…Since the initial model was not well fitted to the data (TLI was slightly below 0.9), the model was modified based on both the modification indices reported by Mplus 8.3 and substantive significance to improve the fit of the model, which was consistent with the literature ( Yu et al, 2011 ; Vervoort et al, 2019 ). In the current study, an error covariance correlation between item 2 (“When I’m doing well at something, I love to keep at it.”) and item 4 (“When I get something I want, I feel excited and energized.”) was allowed.…”
Section: Resultsmentioning
confidence: 86%
“…In other words, the comparison of means between men and women could be problematic if we do not assess the measurement invariance (MI) of the instrument ( Vandenberg and Lance, 2000 ). Some studies have examined the MI of BIS/BAS scales across genders ( Campbell-Sills et al, 2004 ; Morean et al, 2014 ; Pagliaccio et al, 2016 ; Vervoort et al, 2019 ; Toro et al, 2020 ). To date, however, no study has verified MI of the Chinese version of the BIS/BAS scales across gender.…”
Section: Introductionmentioning
confidence: 99%
“…In the present sample, internal consistency of scale is good (Cronbach's  = .84). The BAS-scale gives valid parent-report indices of bottom-up reward sensitivity in children and adolescents, as shown by the meaningful relations with instruments assessing related personality traits and psychopathological symptoms (Vandeweghe, Matton, et al, 2016;Vervoort et al, 2019;Vervoort et al, 2015).…”
Section: Instrumentsmentioning
confidence: 99%